Mesodermal retinoic acid signaling regulates endothelial cell coalescence in caudal pharyngeal arch artery vasculogenesis - Li, Peng (2011)
Disruption of retinoic acid signaling causes a variety of pharyngeal arch artery and great vessel defects, as well as malformations in many other tissues, including those derived from the pharyngeal endoderm. Previous studies implied that arch artery defects in the context of defective RA signaling occur secondary to pharyngeal pouch segmentation defects, although this model has never been experimentally verified. In this study, we examined arch artery morphogenesis during mouse development, and the role of RA in this process. We show in normal embryos that the arch arteries form by vasculogenic differentiation of pharyngeal mesoderm. Using various genetic backgrounds and tissue-specific mutation approaches, we segregate pharyngeal arch artery and pharyngeal pouch defects in RA receptor mutants, and show that RA signal transduction only in pharyngeal mesoderm is required for arch artery formation. RA does not control pharyngeal mesodermal differentiation to endothelium, but instead promotes the aggregation of endothelial cells into nascent vessels. Expression of VE-cadherin was substantially reduced in RAR mutants, and this deficiency may underlie the arch artery defects. The consequences of disrupted mesodermal and endodermal RA signaling were restricted to the 4(th) and 6(th) arch arteries and to the 4(th) pharyngeal pouch, respectively, suggesting that different regulatory mechanisms control the formation of the more anterior arch arteries and pouches.